2018
DOI: 10.1111/jcmm.14004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the urokinase‐type plasminogen activator receptor system recovers STZ‐induced diabetic nephropathy

Abstract: The urokinase‐type plasminogen activator (uPA) receptor (uPAR) participates to the mechanisms causing renal damage in response to hyperglycaemia. The main function of uPAR in podocytes (as well as soluble uPAR ‐(s)uPAR‐ from circulation) is to regulate podocyte function through αvβ3 integrin/Rac‐1. We addressed the question of whether blocking the uPAR pathway with the small peptide UPARANT, which inhibits uPAR binding to the formyl peptide receptors (FPRs) can improve kidney lesions in a rat model of streptoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 61 publications
(143 reference statements)
0
29
0
Order By: Relevance
“…These conclusions are in line with a recent report showing that targeting the urokinase receptor in a rat model of diabetic kidney disease resulted in improvement in kidney function. 42 The mechanisms of suPAR in kidney dysfunction have focused on its source of production and its role in binding and activating podocyte αvβ3 integrins. 15,17 Other reports have suggested that suPAR also affects proximal tubules and drives kidney fibrosis in an integrin-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…These conclusions are in line with a recent report showing that targeting the urokinase receptor in a rat model of diabetic kidney disease resulted in improvement in kidney function. 42 The mechanisms of suPAR in kidney dysfunction have focused on its source of production and its role in binding and activating podocyte αvβ3 integrins. 15,17 Other reports have suggested that suPAR also affects proximal tubules and drives kidney fibrosis in an integrin-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, αvβ3 integrin is upregulated on proliferating endothelial cells during angiogenesis and vascular remodeling [67] and contributes to inflammation by regulating the nuclear factor kappa-light-chain-enhancer of B cells (NF-kB) -induced pro-inflammatory responses [68]. In particular, upregulated levels of αvβ3 integrin are associated to main inflammatory processes in diabetic nephropathy [45], while inflammation-induced expression of αvβ3 integrin regulates astrocyte reactivity [69]. In models of ischemic brain, activation of αvβ3 integrin is associated with the release of inflammatory factors whereas its inhibition has been shown to reduce inflammatory processes [70,71].…”
Section: Upar-co-receptor Interactionmentioning
confidence: 99%
“…There is ongoing research to examine if uPAR is involved in the pathogenesis of proteinuric kidney disease [23, 24]. Increased expression of uPAR mRNA and protein in podocytes was detected in several proteinuric animal models and human glomerular disease, suggesting upregulated uPAR levels in podocytes might contribute to enhanced podocyte migration, foot process effacement, and eventually proteinuria formation [25-29]. Amiloride, a potassium-sparing diuretic via its inhibition on ENaC, has been shown to suppress uPAR expression in podocytes, reduce podocyte cell motility, decrease proteinuria, and attenuate glomerulosclerosis in proteinuric animal models [9, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that amiloride inhibits both uPAR [9, 18] and uPA [37] which are 2 contributors in the pathogenesis of nephrotic syndrome. While uPAR probably is involved in podocyte dysfunction and proteinuria formation [26-29], uPA plays a role in ENaC overactivation and edema formation under nephrotic conditions [30, 31]. Therefore, as a medication blocking 2 pivotal mediators – uPAR and uPA – that are involved in the pathogenesis of proteinuric kidney disease, amiloride and probably triamterene could serve as unique agents to treat proteinuria, edema, and hypertension in these patients.…”
Section: Discussionmentioning
confidence: 99%